THE EFFECT OF ORGANIZATIONAL CULTURE, LEADERSHIP AND MOTIVATION ON WORK PERFORMANCE - RIYANTO, RIYANTO (JURNAL ILMIAH EDUCATIONAL MANAGEMENT, 2011)
Work performance can be demonstrated through independent behavioral attitude as a form of ability to execute duties as school headmaster in achieving the organizational goals. Work performance directly or indirectly influenced by many factors: motivation, leadership and organizational culture. The purpose of this study is to discover on how significant, motivation, leadership and organizational culture influence the SMP headmaster work performance in North Lampung. This study had tested the hypothesis and found that organizational culture, leadership and motivation directly influence the work performance of SMP headmaster of North Lampung. The unit analysis was Public and Private SMP headmaster in North Lampung Regency. The research sample was 80 people from a population of 108 SMP headmasters in North Lampung. In analyzing the data, the research used path analysis. The results showed that organizational culture and leadership directly influence the SMP headmasterâs motivation. Meanwhile, their motivation and school organizational culture directly influence the performance. Hence, leadership directly affects the SMP headmasterâs performance. This means that Ho was refused and H1 was accepted, meaning that organizational culture, leadership and motivation have direct effect on the SMP headmastersâ of North Lampung work performance. The research results imply that to improve ones work performance, he/she should be pursued with motivation, leadership and organizational culture improvement. The better motivation, leadership and organizational culture, the better oneâs work performance would be.Key Words: organizational culture, Leadership, motivation and performance